Development of a water resources assessment and audit framework for Sri Lanka - Matin, Mir Abdul; Smakhtin, Vladimir U.; Palliyaguruge, Mahendra N.; Mohideen, Sadir; Yapa, Nishath; Alankara, Ranjith; Gunasinghe, Sarath; Jayakody, Priyantha (2010)
The demand and use of water resources is permanently increasing, while the quality of water is dropping and the availability of water in the context of climate change is becoming uncertain. To meet these growing problems it is necessary to carefully assess the existing water stocks and future trends in a country. The accuracy of such an assessment highly depends on the quality of data and information used. In other words ? we cannot manage what we do not measure. In most developing countries, the lack of readily accessible and quality controlled data is the major obstacle for scientifically-based assessments on water resources, water development planning and evaluating the status and trends of water resources. Sri Lanka too faces similar obstacles. Recently IWMI initiated the development of a prototype system for managing national water resources data and information, which can be accessed online by various users and interested stakeholders. The data and information in the system is being organized in modules to provide user-friendly access. The ?overview? module includes information on topography, soil, land use, land cover, river network and settlement patterns. The ?water availability? module contains data on various components of the hydrological cycle, including rainfall, runoff, evaporation, ground- water, river basin characteristics, per capita water availability and trends, and water scarcity. The ?Demand and use? module focuses on the factors that affect demand, such as population growth, sectoral demand, irrigation requirements and withdrawals. The ?water quality? module provides information on salinity, water quality constituents and Water related diseases. The ?governance and management? module contains information on institutions, legislation and finances in the Sri Lankan water sector. The ?disaster and risk? module focuses on the characteristics of floods, land slides, tsunami etc. Finally, the ?climate change? module covers the impacts of climate change on rainfall, salinity and sea level rise to guide adaptation planning. The system is designed with a view to facilitate assessments of water resources at various administrative (e.g., province, district) and hydrological (e.g., river basin) units. The map-based interface ensures quick access to available data and allows the date to be downloaded and displayed. The system is currently a ?work in progress? and only an illustration of what can be achieved. It is envisaged that by cooperating with national agencies, the system will be enhanced into a unified platform for maintaining and sharing data by various participating agencies and will be used to conduct a systematic assessment of water resources in Sri Lanka. By developing a comprehensive and national water audit, Sri Lanka may provide as an example to other developing countries too.